Waterfowl migration survey, Missouri River, November 27, 1994 - Iowa State University. Special Collections and University Archives (curator) (1994)
A count of waterfowl at Badger Lake and Snyder Bend. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1994. Plustek - flatbed